Loss of asthma control and activation of coagulation and fibrinolysis. Issue 3 (March 2016) - Sneeboer, M. M. S.; Fens, N.; van de Pol, M. A.; Majoor, C. J.; Meijers, J. C.M.; Kamphuisen, P. W.; Lutter, R.; Sterk, P. J.; Bel, E. H.D.
Summary: Background: Epidemiologic studies have shown that patients with severe asthma have increased risk of pulmonary embolism, in particular patients with frequent asthma exacerbations. Therefore, we hypothesized that asthma exacerbations are associated with increased haemostatic activity. Objective: To investigate whether induced loss of asthma control is associated with changes in coagulation and fibrinolytic parameters in peripheral blood. Methods: We performed a prospective, inhaled steroid withdrawal study in 23 patients with moderate to moderately severe asthma, consisting of a baseline visit and a visit after loss of asthma control. During the visits, we measured asthma control questionnaire (ACQ), atopy, lung function, inflammatory markers (eosinophils and neutrophils), and haemostatic parameters in plasma. Results: Complete cessation of inhaled corticosteroids led to a loss of asthma control in 22 of 23 patients. We found increased asthma symptoms (ACQ 0.9 vs. 2.9, P < 0.01), significantly reduced lung function (forced expiratory volume in 1 s (FEV1 ) 3.51L vs. 3.13L, P < 0.01) and increased levels of eosinophils in plasma (0.26 × 10 E9 /L vs. 0.16 × 10 E9 /L, P = 0.03) in patients after loss of asthma control. However, we observed no significant changes in the coagulation and fibrinolysis parameters. Conclusion: Loss of asthma control after cessation of inhaled corticosteroids does not lead to increased haemostatic activation in patients with moderate to moderately severe asthma. This suggests that more severe inflammation or additional risk factors are required for activation of coagulation or reduction of fibrinolysis in asthma.